Pemikiran Imam Nawawi terhadap Pendidikan Indonesia - Khoir, Mulyanto Abdullah; Hadiwijaya, Lalu Firman (Lembaga Yasin AlSys, 2025)
This research examines the relevance of Imam Nawawi's educational thoughts in the context of contemporary Indonesian education. Through a qualitative approach with library research methods, this study analyzes Imam Nawawi's holistic educational concept that integrates intellectual, spiritual, and social dimensions. The results indicate that Imam Nawawi's thoughts have significant relevance in developing the national education system, particularly in character formation and integrating traditional values with modern demands. The implementation of Imam Nawawi's educational principles in contemporary learning has proven to enhance not only academic achievement but also students' spiritual maturity. Digital transformation in education can be effectively integrated with the fundamental values of Imam Nawawi's thoughts, creating a comprehensive learning model that adapts to contemporary developments. This research provides theoretical and practical contributions to developing an educational system that combines traditional values with modern educational needs.